Rivaroxaban Reduces the Dabigatran Dose Required for Anticoagulation During Simulated Cardiopulmonary Bypass. (7th April 2022) - Nadtochiy, Sergiy M.; Stefanos, Tatsiana; Angona, Ronald E.; Lebedko, Natalie; Baldzizhar, Aksana; Feng, Changyong; Eaton, Michael P.
Abstract : BACKGROUND: Heparin is the standard anticoagulant for cardiopulmonary bypass (CPB); however, there are problems with its use that make the development of suitable alternatives desirable. Currently, no ideal alternative exists. We have previously reported that the direct thrombin inhibitor dabigatran can prevent coagulation in simulated CPB at high concentrations. These high concentrations may cause difficulties in achieving the reversal of dabigatran with idarucizumab, given the markedly different pharmacokinetics of the 2 drugs. Herein, we test the hypothesis that the addition of the anti-Xa drug rivaroxaban would provide suitable anticoagulation at a lower concentration of dabigatran given likely synergy between the 2 classes of drugs. The primary goal of the study was to investigate whether the addition of rivaroxaban reduces the concentration of dabigatran necessary to allow 2 hours of simulated CPB. METHODS: The study was performed in sequential steps. Blood collected from consenting healthy donors was used throughout. First, we added graded concentrations of dabigatran and rivaroxaban alone and in combination and assessed inhibition of anticoagulation using thromboelastometry. Using results from this step, combinations of dabigatran and rivaroxaban were tested in both Chandler loop and simulated CPB circuits. Dabigatran and rivaroxaban were added before recalcification, and the circuits were run for 120 minutes. In both models of CPB, 120 minutes of circulation without visible thrombus was considered successful. In the Chandler loop system, idarucizumab was added to reverse anticoagulant effects. In the CPB circuits, the arterial line filters were examined using scanning electron microscope (SEM) to qualitatively assess for fibrin deposition. RESULTS: In vitro analysis of blood samples treated with dabigatran and rivaroxaban showed that dabigatran and rivaroxaban individually prolonged clotting time (CT) in a dose-dependent manner. However, when combined, the drugs behaved synergistically. In the Chandler loop system, dabigatran 2400 and 4800 ng/mL plus rivaroxaban (150 ng/mL) effectively prevented clot formation and reduced the dynamics of clot propagation for 120 minutes. Idarucizumab (250–1000 µg/mL) effectively reversed anticoagulation. In the CPB circuits, dabigatran (2500 ng/mL) and rivaroxaban (200 ng/mL) were successful in allowing 120 minutes of simulated CPB and prevented fibrin deposition. Biomarkers of coagulation activation did not increase during simulated CPB. Heparin controls performed similarly to dabigatran and rivaroxaban. CONCLUSIONS: The dual administration of oral anticoagulant drugs (dabigatran and Rivaroxaban) with different pharmacologic mechanisms of action produced synergistic inhibition of coagulation in vitro and successfully prevented clotting during simulated CPB.